Expansion of Small and Enterprises Loans at Bank for Investment and Development of Vietnam, JSC, West Hanoi Branch - Doan, Thi Huong (H. : ĐHQGHN, 2020)
the subject matter includes the following three chapters: • Chapter 1: General Information about small and medium enterprises loans at a commercial bank. • Chapter 2: Current Realities of small and medium enterprises loans at the Bank for Investment and Development of Vietnam, West Hanoi Branch. • Chapter 3: Solutions to expand the small and medium enterprises loans at the Bank for Investment and Development of Vietnam, West Hanoi Branch.